PENGARUH PENEMPATAN KARYAWAN DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN (Studi Kasus Karyawan Pada BPJS Ketenagakerjaan Cabang Kota - Nurhadi, Galih; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine how the effect of employee placement and compensation on employee job satisfaction on employees of the BPJS Employment Branch of Pekanbaru City. The population in this study were permanent employees of the BPJS Employment Office in the Pekanbaru City Branch. Sampling using saturated or census samples with a sample of 41 employees. Research data collection in the form of primary data, with the distribution of questionnaires as research instruments and secondary data in the form of company archives. Analysis of the data used is to use simple and multiple linear regression, determination test, t test, f test with the help of SPSS program. Hypothesis testing uses simple linear analysis methods and multiple linear analysis with the results showing that employee placement and compensation have a positive and significant effect on job satisfaction at the BPJS Employment Branch in Pekanbaru City. With the calculation of the coefficient of determination (R2) the effect of employee placement on job satisfaction obtained a square value of 0.399 or 39.9% and the effect of compensation on job satisfaction obtained a square value of 0.793 or 79.3% and the calculation of determination (R2) multiple the effect of employee placement and compensation on job satisfaction obtained a square value of 0.822 or 82.2%. This shows that employee placement and compensation have an effect of 82.2% on job satisfaction, while the remaining 17.8% is influenced by other variables not examined in this studyÂ Keywords: Employee Placement, Compensation, Job Satisfaction